The integration of creative programming in experimental music and digital art - Pratt, Matthew (College of Music, 2026)
This explication presents an overview of the background, composition processes and influences involved in the creation of experimental music and digital art using creative programming. By establishing the context of my composition style, the paper will outline the methods, conceptualization and creative language used in the creation of a work of experimental music. It will also touch on the use of creative programming in digital art.